The Probative Power of Deepfake-Based Electronic Evidence in Fraud Crimes - Wahyu Slamet Permadi; Aries Isnandar; Yogi Prasetyo (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2026)
Advances in artificial intelligence technology, especially deepfakes, pose serious problems for the system of evidence in criminal law, particularly in the handling of digital-based fraud. Audio and visual manipulation that increasingly resembles authentic conditions has the potential to undermine the authenticity and integrity of electronic evidence, increase the possibility of misrepresentation, and hinder efforts to achieve material truth and legal certainty. This study aims to analyze the legal position and evidentiary value of deepfake-based electronic evidence in criminal fraud cases according to the Indonesian positive law framework, as well as to formulate a model for assessing the reliability of electronic evidence that is responsive to the dynamics of artificial intelligence development. This research uses a normative legal research method through a legislative, conceptual, and comparative approach. Primary and secondary legal materials are analyzed qualitatively through a review of national norms regarding electronic evidence and a comparison of digital evidence practices in a number of other jurisdictions. The findings of the study show that normative recognition of electronic evidence in Indonesian criminal procedure law is already available, while technical regulations related to authentication and evaluation of the reliability of artificial intelligence-based electronic evidence, particularly deepfakes, have not been specifically formulated. The absence of specific technical regulations weakens the material strength of evidence and places the assessment of judges and digital forensic experts as the main determining factors. The urgency of strengthening criminal procedure law is emphasized through the application of the Electronic Evidence Reliability Framework (EERF), which integrates digital forensic verification, metadata validation, and the continuity of the chain of custody of electronic evidence to ensure justice, legal certainty, and the protection of the rights of the parties in the criminal justice process.